Conservative Management of Cervical Pregnancy with the Administration of Methotrexate and Potassium Chloride: A Case Report - Mojgan Javedani Masroor; Anna Zarei; Hossein Sheibani (Case Reports in Obstetrics and Gynecology)
Background. Cervical pregnancy is a rare form of ectopic pregnancy in which the fetus implants and grows inside the endocervical canal. This report aims at introducing a case of successful conservative management of cervical ectopic pregnancy. Case presentation. The patient was a 35-year-old woman, who had received treatment for primary infertility for 5 years. She complained of painless bleeding on day 37 of gestational age with a start point from 10 days before. The patient had stable vital signs and was referred to Shahid Akbar Abadi Hospital in Tehran affiliated with the Iran University of Medical Sciences. In the ultrasonography, the pregnancy sac and the yolk sac with the embryonic pole with a positive fetal heart rate were presented and located near the internal os, so the cervical pregnancy was diagnosed, and after treatment with intramuscular methotrexate and intra-amniotic administration of potassium chloride, a gradual decrease in β-HCG levels was observed without the need for additional interventional treatment. Conclusion. The primary takeaway of our report is that the conservative treatment, including intramuscular methotrexate and intrauterine potassium chloride administration, may be effective in treating cervical pregnancy that can be detected early without the use of curettage.